Security in wireless mesh networks - Zhang, Yan; Zheng, Jun; Hu, Honglin (Wireless networks and mobile communications, 2009)
Wireless mesh networks (WMN) encompass a new area of technology set to play an important role in the next generation wireless mobile networks. WMN is characterized by dynamic self-organization, self-configuration, and self-healing to enable flexible integration, quick deployment, easy maintenance, low costs, high scalability, and reliable services. To achieve these aims, security mechanisms are essential to ensure trusted on-going communications. Security in Wireless Mesh Networks explores key security challenges set in diverse scenarios, as well as emerging standards that include authentication, access control and authorization, attacks, privacy and trust, encryption, key management, identity management, DoS attacks, intrusion detection and prevention, secure routing, and security policies. The book also examines security mechanisms in IEEE 802.11, IEEE 802.15, IEEE 802.16, and IEEE 802.20 standards. In addition, it provides numerous case studies and applications to facilitate understanding. As a single, comprehensive guide to security-related issues in WMN, this book is an important resource to have if you are working on the design, selection, and implementation of wireless mesh networks and system components.